2020
DOI: 10.1186/s13567-020-00773-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mapping of the cell response to E. coli infection in porcine intestinal epithelial cells pretreated with exopolysaccharide derived from Lactobacillus reuteri

Abstract: Bacterial exopolysaccharides (EPSs) are known to modulate immunity. To date, a plethora of studies have reported the effect of EPSs on intestinal cells; however few works have revealed a complete picture of the signalling events in intestinal epithelial cells induced by bacterial EPSs. Here, using transcriptomics, we comprehensively mapped the biological processes in porcine intestinal epithelial cells challenged with EPS derived from Lactobacillus reuteri alone, enterotoxigenic Escherichia coli (ETEC) or ETEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Escherichia coli LPS binding to TLR4 promotes activation of downstream TRIF-dependent and MyD88-dependent pathways, which in turn induces production of a cascade of activated molecules, such as NF-κB, AP-1, and inflammatory cytokines ( 22 ). Consistent with the present study, enriched TLR and NF-κB signaling pathways are also found in porcine IECs infected with various ETEC strains ( 9 , 21 ). NF-κB contains a family of transcription factors, which functions in regulating various biological responses, including proliferation, cell apoptosis, and invasiveness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Escherichia coli LPS binding to TLR4 promotes activation of downstream TRIF-dependent and MyD88-dependent pathways, which in turn induces production of a cascade of activated molecules, such as NF-κB, AP-1, and inflammatory cytokines ( 22 ). Consistent with the present study, enriched TLR and NF-κB signaling pathways are also found in porcine IECs infected with various ETEC strains ( 9 , 21 ). NF-κB contains a family of transcription factors, which functions in regulating various biological responses, including proliferation, cell apoptosis, and invasiveness.…”
Section: Discussionsupporting
confidence: 92%
“…Comparable studies have shown that ETEC induced typical immune-related signaling pathways in porcine IECs, but the extent of the inflammatory response is different due to the difference in ETEC strain, infection time, infection concentration, and cell lines. The cell junction organization and extracellular matrix organization terms are enriched in the DEGs of ETEC strain 11501-infected IPEC-1 cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Xie et al, the authors creatively developed a new type of L. reuteri— a bovine lactoferricin-lactoferrampin (LFCA)-encoding L. reuteri CO21 (LR-LFCA) and finally demonstrated that LR-LFCA can function in the following three aspects in a newborn ETEC-infected piglet intestine model: (1) it could enhance gut immune responses by improving intestinal barrier function and gut microbiota composition, (2) it was able to protect the gut from oxidative stress by activating the NRF2/HO-1 pathway, and (3) it had the ability to inhibit the NF-κB pathway to perform its anti-inflammatory effect (Xie et al, 2021 ). Further, Tkáčiková et al ( 2020 ) found that the pretreatment of L. reuteri L26 Biocenol (CCM 8616)-derived bacterial exopolysaccharides (EPSs) can attenuate the overexpression of the genes induced by ETEC infection to suppress inflammatory responses. Human-derived L. reuteri strains (ATCC PTA 6475, DSM 17938, and 1563F), a rat strain (R2LC), and piglet-derived L. reuteri (HCM2 and LR1) were also able to reduce the detrimental effect of ETEC (Karimi et al, 2018 ; Wang et al, 2018 ; Yi et al, 2018a ).…”
Section: Infection-associated Intestinal Diseasesmentioning
confidence: 99%
“…If the intestinal epithelial cells are seriously damaged, the self-repair of the intestinal tract becomes difficult (18). Cytokines, including IL-18, IL-10 and IL-6, have been proven to play important roles in local inflammation, repair and damage of tissues (19). However, the role of the IL-6/STAT3 signaling pathway on intestinal injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%